A fatal case of infant oral mutilation practice - Arthur Musakulu Kemoli; Immaculate Achieng Opondo (Wolters Kluwer Medknow Publications, 2021)
Infant oral mutilation (IOM) is a traditional dental practice where traditional healers enucleate primary canine tooth buds in children in the hope of preventing or curing childhood illness. The method applied is heinous, painful, and carried out in unsterile environment, and this increases the morbidity and mortality of children from the communities where IOM is rife. The case report described here arose from a village, where an infant with a medical issue ended up in the hands of a local traditional healer who enucleated her four primary canine tooth buds. The traditional treatment resulted in the fatality of the child in <24 h of the procedure, a testimony that some traditional therapeutic procedures have no place in managing common childhood illnesses.